Delayed Onset and Prolonged ECT-Related Delirium - Hassamal, Sameer; Pandurangi, Ananda; Venkatachalam, Vasu; Levenson, James (Case Reports in Psychiatry, 2013)
Electroconvulsive therapy (ECT) is effective in the treatment of depression. Delayed post-ECT delirium is rare but can occur in a small subset of patients with risk factors and in most cases resolves with the use of psychotropic medications. We report a unique presentation of a patient who developed a delayed post-ECT delirium with fecal incontinence that commenced 24 hours after the administration of ECT. The condition resolved spontaneously after 48 hours without the use of psychotropic medications.